Kerja Sama Pemerintah Daerah dengan Badan Usaha Konservasi Energi untuk Efisiensi Energi di Sektor Penerangan Jalan Umum (PJU) - Melati Ayuning Pranasari; Ray Ferza (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
The implementation of energy conservation for energy efficiency and Public Street Lighting (PJU) has not run optimally. Several previous studies have presented technological options and economic policies for the implementation of energy conservation for energy efficiency in the Public Road Lighting sector. While to strengthen energy efficiency policies, the Government has a regional government cooperation policy with business entities. This study aims to analyze the implementation and problems of PPP policy (Government Cooperation with Business Entities) Energy Conservation for Energy Efficiency in the PJU sector. The method used in this study is a qualitative method with a descriptive approach. This study produces conclusions as follows. In its implementation, the energy conservation PPP policy for energy efficiency and PJU has been carried out by the local government and proven to be able to reduce the burden on local governments in financing the management of PJU, especially the cost / budget efficiency of the PJU in the APBD. The implementation of energy conservation PPP policy is included in the category of complex cooperation because the mechanism for payment of energy efficiency services is based on payment from saving, the Government does not cover the initial costs (zero investment) and does not bear the risk of state losses ( zero risk). Business entities that will bear the risk of financial losses due to technical implementation if they cannot prove the existence of savings. The PPP policy issues that emerged included the absence of technical guidelines related to the implementation of PPP on the initiative of energy conservation business entities for energy efficiency and PJU, in which the unsolicited project PPP scheme has not found a potential complaint/ indication of state financial losses because so far still fulfills the principle of prudence.